INOVASI KUE TRADISIONAL DALAM KEMASAN MODERN:PELUANG BISNIS CHOCOLATE CORNNUT KEKINIAN - Fadhilatunnisa, Rima; Hidayat, Karyadi; Dwi Lestari, Annisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This article analyzes the business potential of "Chocolate Cornnut," a culinary innovation that combines chocolate, corn, and coconut, creating a unique visual appeal and flavor from local ingredients. Through a literature review, this research identifies a promising market opportunity in Indonesia, supported by the innovation's flexibility and broad consumer appeal. This business has the potential to empower the local economy and create jobs. Despite challenges such as competition and fluctuating raw material prices, success can be achieved through continuous innovation, an omnichannel marketing strategy, efficient supply chain management, and a focus on customer experience. This analysis, based on innovation and entrepreneurship theories, including Schumpeter's concepts, demonstrates that Chocolate Cornnut offers sustainable business growth and positive socio-economic impacts.